Corrosion Inhibitors 2019
DOI: 10.5772/intechopen.80542
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibitors

Abstract: Corrosion is a natural process driven by energy consideration. Inhibition is a preventive measure against corrosive attack on metallic materials. Corrosion inhibitors have been frequently studied, since they offer simple solution for protection of metals against corrosion in aqueous environment. Mineral acids like hydrochloric and sulfuric acids are most widely used in pickling baths to remove the metal oxides formed on the surface. The multidisciplinary aspect of corrosion problems combined with the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…The corrosion occurs, in an aqueous or wet environment, when the metal is in contact with an electrolytic conducting liquid or when two dissimilar metals or alloys are either immersed or dipped partially in the electrolytic conducting solutions [20].…”
Section: Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corrosion occurs, in an aqueous or wet environment, when the metal is in contact with an electrolytic conducting liquid or when two dissimilar metals or alloys are either immersed or dipped partially in the electrolytic conducting solutions [20].…”
Section: Corrosionmentioning
confidence: 99%
“…An appropriate green corrosion control can help to avoid many potential disasters that can cause serious issues including life-loss, negative social impacts, water resource and environmental pollution. In this way green corrosion inhibition studies have become oriented towards human health and safety considerations [14,20]. However, different studies have shown that green corrosion inhibition effect is usually found to be very low compared to synthetic organic inhibitors [10].…”
Section: Introductionmentioning
confidence: 99%
“…𝐶 𝑖𝑛ℎ 𝜃 = 1 𝐾 𝑎𝑑𝑠 + 𝐶 𝑖𝑛ℎ [10] K is the binding constant of the adsorption reaction and C inh is the inhibitor concentration in corrosive solution. K can be associated to the standard free energy of adsorption ∆G • ads via the following equation:𝐾 ads = ( ) .…”
Section: 4adsorption Isothermmentioning
confidence: 99%
“…Several factors affect the adsorption behavior, such as the metal's nature and its surface voltage, the inhibitor's chemical composition, the form of a corrosive medium, and the corrosion reaction temperature. Both chemical-and physicalsorption are primarily the interaction mechanisms of the inhibitor-metal at the interface [10]. The organic molecules' adsorption on the metal surface attributes to their electron-donating ability that relating to the presence of π-orbitals, aromaticity, and functional groups such as amines and carbonitrile, which reveal high performance in corrosion inhibition [1,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion is the progressive oxidation and degradation of metallic and non-metallic materials by chemical and/or electrochemical interaction reaction with their environment [1][2][3]. Refined metals being in a higher energy state release energy thus reverting to their natural chemically combined state of lower energy in the form of ores and stable compounds [4,5]. Corrosion damage has been a major economic and industrial problem necessitating research into solutions to mitigate it.…”
Section: Introductionmentioning
confidence: 99%